Treatment Terhadap Anak Yatim dalam Al-Qur’an - Ahmad Musyafiq; Ikhlasul Amal; Fajar Imam Nugroho (Universitas Darussalam Gontor, 2022)
The number of orphans has increased dramatically due to the coronavirus pandemic as an ongoing global pandemic. Yet, the treatment of orphans is still far from what is expected while orphans need a party who can stand in for their socio-psychological needs. The proper treatment of orphans has a positive impact on the continuity of the orphans themselves. It is crucial to note that the verses of the Quran draw attention to the treatment of orphans. In most cases, children who were fatherless had more negative tendencies than others. In this paper, a variety of treatments for orphans are shown using thematic methods by summarizing the verses of the Quran that contain the meaning of orphans at one time. it was revealed that the word orphan occurs 9 times in the singular and 13 times in the plural. From the study of 22 terms for orphans and their derivatives, it was found that treatment of orphans can be carried out in groups or individually with the aim of improving the condition of orphans both in terms of their physical and psychological needs. The treatment of orphans is not only to satisfy consumption needs but also to impart skills so that the orphans can be productive, independent, and responsible. On the other hand, caregivers are sincere and trustworthy when treating orphans.